2019
DOI: 10.1002/adbi.201900091
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Mechanoactivation of Wnt Signaling Augments Dopaminergic Differentiation of Neuronal Cells

Abstract: Wnt signaling is a key developmental pathway that regulates dopaminergic progenitor cell proliferation and differentiation during neuronal development. This makes Wnt signaling an important therapeutic target for neurodegenerative conditions such as Parkinson's disease. Wnt signaling can be modulated using peptides such as UM206, which bind to the Wnt receptor Frizzled. Previous work has demonstrated remote activation of the Wnt pathway through Frizzled using peptide‐functionalized magnetic nanoparticles (MNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…1G). Functionalized nanoparticles can also be used to activate specific cell surface mechanoreceptors and initiate their signaling response [98,99] (Fig. 1H).…”
Section: To Control Cell Functionmentioning
confidence: 99%
“…1G). Functionalized nanoparticles can also be used to activate specific cell surface mechanoreceptors and initiate their signaling response [98,99] (Fig. 1H).…”
Section: To Control Cell Functionmentioning
confidence: 99%
“…For example, it was shown that classical iron oxide microparticles which are commercially available (2.8 μm; Dynabead) coated with wheat germ agglutinin (WGA) can generate 30 pN per microparticle under a rotating DC field of 200 mT. 33 Other big magnetic actuators, such as 250 nm magnetite MNPs were capable of activating intracellular pathways in a neuronal cell line 34 and in mesenchymal cells 35 by generating mechanical forces of about 10 -12 pN. Moreover, a positive correlation between size and exerted mechanical force was reported for a set of magnetite particles ranging from 250 nm to 2.7 μm in diameter, which could generate mechanical forces between 0.2 to 38.9 pN per particle depending on their size.…”
Section: Iron Oxide and Doped Ferrite Nanoparticlesmentioning
confidence: 99%
“…Rotherham et al showed that remote activation of UM206 by MNPs with magnetic field stimulation was feasible to activate Wnt/β-catenin pathway, promoting bone formation in chicks, and dopaminergic marker expression in rats' neurons 41,42 . This makes Wnt signaling an important therapeutic target for neurogenerative disease such as Parkinson's disease 42,43 . c. Recombinant Norrin Norrin is another cysteine-rich secreted protein, encoded by NDP gene, that binds with high affinity and specificity to FZD4 and LRP5/6, activate Wnt/β-catenin 44 , and has angiogenic and neuroprotective properties 45,46 .…”
Section: Activation Of Wnt Signaling Through Wnt Proteins and Wnt Mimics A Wnt Proteinsmentioning
confidence: 99%